Testing the Olze and Timme Methods for Dental Age Estimation in Radiographs of Brazilian Subadults and Adults - Thaís Uenoyama Dezem; Ademir Franco; Carlos Eduardo Machado Palhares; Alexandre Raphael Deitos; Ricardo Henrique Alves da Silva; Bianca Marques Santiago; Isabella Lima Arrais Ribeiro; Eduardo Daruge Junior (University of Zagreb. School of Dental Medicine, 2021)
Aim: This study aimed to test the applicability of the methods proposed by Olze et al. (2012) and Timme et al. for dental age estimation in Brazilian subadults and adults. Material and methods: Panoramic radiographs of 503 individuals aged between 20 and 70 years were analyzed. The mean chronological age of males and females of the sample was 29.04 and 29.97 years, receptively. Secondary dentin formation, cementum apposition, periodontal recession, and attrition of teeth #34, #35, #44 and #45 teeth were assessed as parameters to be calculated in the formulae designed by Olze et al. and Timme et al. Results: In males, the mean estimated age by the Olze method was 28.97 ± 2.86 years, while in females it was 27.85 ± 2.70 years. The Timme method estimated mean age for males of 32.54 ± 5.32 years and for females 33.09 ± 5.16 years. Low coefficients of determination (r 2 ) for the application of tooth-specific formulae of both methods suggest that estimated and chronological ages were not properly associated. Conclusion: The outcomes of this study indicate that the Olze and Timme methods may be limited for forensic applications in Brazilian subadults and adults. Country-specific statistical adjustments might be useful for improvements in practice